2021
DOI: 10.1103/physrevb.104.064101
|View full text |Cite|
|
Sign up to set email alerts
|

Local structure of Mott insulating iron oxychalcogenides La2O2Fe2OM2(M=et al.

Abstract: We describe the local structural properties of the iron oxychalcogenides, La 2 O 2 Fe 2 OM 2 (M = S, Se), by using pair distribution function analysis applied to total scattering data. Our results from neutron powder diffraction show that M = S and Se possess similar nuclear structures at low and room temperatures. The local crystal structures were studied by investigating deviations in atomic positions and the extent of the formation of orthorhombicity. Analysis of the total scattering data suggests that buck… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The magnetic structure of La 2 O 2 Fe 2 OQ 2 is stabilized by antiferromagnetic Fe–O–Fe stripes, which are coupled by ferromagnetic Fe–Se–Fe interactions. , Short-range orthorhombic distortions associated with Fe and O were found in La 2 O 2 Fe 2 OSe 2 with neutron pair distribution function analysis. Such short-range distortions may play an important role in Fe-based superconductivity …”
Section: Quaternary Oxychalcogenidesmentioning
confidence: 99%
“…The magnetic structure of La 2 O 2 Fe 2 OQ 2 is stabilized by antiferromagnetic Fe–O–Fe stripes, which are coupled by ferromagnetic Fe–Se–Fe interactions. , Short-range orthorhombic distortions associated with Fe and O were found in La 2 O 2 Fe 2 OSe 2 with neutron pair distribution function analysis. Such short-range distortions may play an important role in Fe-based superconductivity …”
Section: Quaternary Oxychalcogenidesmentioning
confidence: 99%
“…In some cases, the local structure is well-described by the crystalline model, and it can be concluded that the local and average structure are the same. However, this is not the case in a variety of materials. , In these cases, areas of the PDF that are not well-described by the crystallographic structure can provide insight into the nature of a local distortion, for example an M–O peak (i.e., a bond length) that shows a large discrepancy between the data and the fit.…”
Section: Strategies For Least-squares Analysis Of Total Scattering Datamentioning
confidence: 99%
“…To search for more abundant exotic quantum states associated with the Mott transition, we focused on an iron oxychalcogenide compound La 2 O 3 Fe 2 Se 2 , a well-known Mott insulator. The structure of La 2 O 3 Fe 2 Se 2 has a close relationship with the Fe-based high-Tc superconductor, and the 3d electrons of iron play a key role in the physical properties of both materials [18][19][20][21][22][23][24][25][26][27][28][29] . The Fe 2 O transition-metal layers are a rare example of the anti-CuO 2 type and can also be described as a network of face-sharing octahedra, where the transition-metalcentered octahedron is made up of two axial oxide ions and four equatorial selenide ions.…”
mentioning
confidence: 99%